Penyebaran Penyakit Malaria Model SIRS-SI dengan Pengobatan, Vaksinasi, dan Penyemprotan - Asri Setyowati (MATHunesa: Jurnal Ilmiah Matematika, 2020)
Malaria is a disease that is transmitted through the mosquito type Anopheles females. Spread of malaria to human disease is caused by mosquito bites of infectious carriers. Malaria viruses can also be transmitted through blood transfusions from humans infected to healthy humans. The method is to study issues related to malaria, create constraint issue, determine the assumptions used for model validation and reconstruct the model for the spread of malaria disease. The research aims to reconstruct a model for the spread of malaria diseases with treatment, vaccination and spraying based on the SIRS-SI epidemic model. SIRS are models for human populations when recovering can be re-susceptible to human immune loss, and SI is a model for mosquitoes where assumed mosquito-carrying infections cannot be recovered